Communal discernment in the early church - De Villiers, Pieter G. R. (Faculty of Theology, University of the Free State, 2013)
This article investigates the often-neglected communal dimension of discernment by focusing on the way in which the early church responded to the controversy about the circumcision for gentiles in Acts 15. It analyses how discernment takes place mostly in times of ambiguity and crisis in which a faith community is challenged to seek the divine will. The article then investigates the way in which discernment takes place: it is first and foremost a communal matter which brings together all parties in order to participate in intense debate and weighing of possibilities. Before examining the awareness that discernment is about a contemplative gaze, the article analyses the way in which wisdom of community leaders and wisdom of the past play a role in discerning the right way. Discernment is the ability to see the revelatory meaning in the ongoing process of one’s own or another’s life; to see, as the saints say, “with the eyes of faith” the salvific significance of what seem to be ordinary events (Schneiders 1982:49).
Keywords: Discernment; Early church; Acta 15